2018
DOI: 10.1248/bpb.b18-00267
|View full text |Cite
|
Sign up to set email alerts
|

Romaine Lettuce/Skullcap Mixture Improves Sleep Behavior in Vertebrate Models

Abstract: The aim of this study is to investigate the effects of romaine lettuce leaves extract (RE), skullcap root extract (SE) and their mixture on sleep behaviors in vertebrate models. HPLC analysis showed that RE contains lactucopicrin (0.02±0.01 mg/g extract), chlorogenic acid (4.05±0.03 mg/g extract), caffeic acid (2.38±0.03 mg/g extract), and chicoric acid (7.02±0.32 mg/g extract) as main phenolic compounds, while SE includes baicalin (99.4±0.5 mg/g extract), baicalein (8.28±0.21 mg/g extract), and wogonin (3.09±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Research has indicated that many herbal extracts are ligands of the GABA A receptors in the central nervous system (CNS) and bind to the benzodiazepine binding site, resulting in sleep modulating actions. 15,29) Flumazenil, known as an antagonist of benzodiazepine, is a water-soluble imidazobenzodiazephine that acts antagonistically with benzodiazepine in the gamma-amino-butyric acid type A (GABA A ) receptors in the CNS. 30) Therefore, by treating with the 3 H-labeled flumazenil, we investigated whether GABA A -BDZ receptor response is involved in a GRE-mediated sleep promoting effects, and as a result demonstrate that GRE effectively binds to GABA A receptors to promote sleep time (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has indicated that many herbal extracts are ligands of the GABA A receptors in the central nervous system (CNS) and bind to the benzodiazepine binding site, resulting in sleep modulating actions. 15,29) Flumazenil, known as an antagonist of benzodiazepine, is a water-soluble imidazobenzodiazephine that acts antagonistically with benzodiazepine in the gamma-amino-butyric acid type A (GABA A ) receptors in the CNS. 30) Therefore, by treating with the 3 H-labeled flumazenil, we investigated whether GABA A -BDZ receptor response is involved in a GRE-mediated sleep promoting effects, and as a result demonstrate that GRE effectively binds to GABA A receptors to promote sleep time (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral cortical membranes of male SD rats were prepared in cold Tris-HCl buffer (30 mM, pH 7.4) following a previous report. 15) For membrane-binding experiments, 33. with ice-cold buffer. Radioligands bound to the membrane were counted by a Hidex 300SL counter (Hidex, Finland).…”
Section: Assay Of Lactucin and Lactucopicrinmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, lettuce seed extracts were reported to exert anti‐inflammatory effects in an animal model, the carrageenan‐induced hind paw edema assay (Ismail & Mirza, 2015; Sayyah et al., 2004). Moreover, a mixture of lettuce seeds and skullcap root improved sleep behavior in vertebrate models and could potentially be used to treat sleep disorders (Hong et al., 2018).…”
Section: Potential Benefits For Human Healthmentioning
confidence: 99%
“…Wogonin, the primary chemical constituents of this herb, is flavone derivatives containing a phenylbenzopyrone nucleus. As part of the screening of conventional herbal extracts for benzodiazepine-like activity, it was reported that several flavonoids isolated from this herb exhibited moderate affinities for the GABA (γ-aminobutyric acid) A receptor ( Afzal et al, 2012 , Gupta et al, 2017 , Hong et al, 2018 ). There is increasing evidence that wogonin could afford neuroprotection against oxidative stress-induced brain insult.…”
Section: Introductionmentioning
confidence: 99%